Motives that Mediate the Associations Between Relationship Satisfaction, Orgasmic Difficulty, and the Frequency of Faking Orgasm. Issue 6 (14th September 2022) - Hevesi, Krisztina; Horvath, Zsolt; Miklos, Eszter; Sal, Dorottya; Rowland, David L.
Abstract: Introduction: Faking orgasm by women reportedly occurs quite frequently, with both relationship characteristics and orgasmic difficulty being significant predictors. Aim: We explored women's motives that might mediate the associations between orgasmic difficulty and relationship satisfaction on the one hand, with the frequency of faking orgasm on the other. Methods: In a study of 360 Hungarian women who reported "ever" faking orgasm during partnered sex, we assessed the direct and indirect (mediated) associations between orgasmic difficulty, relationship satisfaction, and the frequency of faking orgasm. Outcomes: Determination of motives that mediate the association between orgasmic difficulty and the frequency of faking orgasm, and the association between relationship satisfaction and the frequency of faking orgasm. Results: Increased orgasmic difficulty was directly related to increased frequency of faking orgasm (β = 0.37; P < .001), and each variable itself was related to a number of motives for faking orgasm. However, the only motive assessed in our study that mediated the relationship between orgasmic difficulty and the frequency of faking orgasm was insecurity about being perceived as abnormal or dysfunctional (indirect effect: β = 0.13; P < .001). A similar pattern emerged with relationship satisfaction and frequency of faking orgasm. These two variables were directly related in that lower relationship satisfaction predicted higher frequency of faking orgasm (β = -0.15; P  = .008). Furthermore, while each variable itself was related to a number of motives for faking orgasm, the only motive assessed in our study that mediated the relationship between the 2 variables was insecurity about being perceived as abnormal or dysfunctional (indirect effect: β = -0.06; P  = .008). Clinical Translation: Insecurity related to being perceived as abnormal or deficient, along with sexual communication, should be addressed in women with a history of faking orgasm but who want to cease doing so. Strengths and Limitations: The sample was relatively large and the online survey adhered to best practices. Nevertheless, bias may result in sample characteristics when recruitment is achieved primarily through social media. In addition, the cross-sectional sample prevented causal determination and represented Western-based values. Conclusions: The associations between orgasmic difficulty and faking orgasm, and between relationship satisfaction and faking orgasm, are both direct and indirect (mediated). The primary motive for mediating the indirect association between the predictor variables and the frequency of faking orgasm was the insecurity about being perceived as deficient or abnormal.